Structural and biochemical evidence supporting poly ADP-ribosylation in the bacterium Deinococcus radiodurans - Chao-Cheng Cho (Nature Portfolio, 2019)
Poly-ADP-ribosylation (PARylation) is a well-known regulatory event in eukaryotes but has not yet been observed in bacteria. Here, the authors solve the structure of a bacterial PAR-glycohydrolase and provide evidence for a prokaryotic PARylation machinery involved in the response to genotoxic stress.